Biodiesel de fontes alternativas de triacilgliceróis : o estudo do teor de ésteres - Oliveira, Valéria Lima (2015)
This study aimed to characterize chemically biodiesel derived from waste oils and fats, and also optimize the methodology for determining the ester content. The methyl biodiesel were obtained from residual frying oil, sewage scum, grease trap, cottonseed oil and oils from the Annonacia family of plants, more specifically the Annona salzmannii, vepretorum and squamosa species. We also investigated the potencial to produce biodiesel from oils obtained from exotic plants like Annona salzmannii, vepretorum and squamosa species. The tested ethyl biodiesel was produced from residual frying oil. The curves TG/DTG of biodiesel samples showed mass losses by evaporation and decomposition of esters. Infrared spectra showed high intensity of absorption bands (1739-1770 cm-1) attributed to C=O stretching ester; confirmed by C-O ester stretch (1247-1034 cm-1). For most samples of biodiesel tested the acid value was in accordance with the limit established by ANP. The study ester content was determined by gas chromatography using the external and internal standardization, using the esters C17:0 and C18:1 as standards. The method with PTV injection, heptane and external standardization using the standard C18:1 showed the best repeatability (0.62%) and reproducibility (3.00%), both with a correlation coefficient of r2= 0.9991. The results of the esters content obtained from the samples showed values between 75 and 93%. Using the method with classical column using silica as adsorbent was observed an increase in the ester content of the samples, reaching the value required by legislation. The comprehensive two-dimensional chromatography has been used in proving the absence of co-eluting compounds that would compromise the determination of the ester content. The supercritical method, using ethanol, proved to be an effective process for alternative raw materials. High conversion rates were obtained (~93%) employing a raw material with a high content of free fatty acids. We observed that with increasing temperature there is a reduction in ester content and that using hexane as co-solvent there was high yield in ester content.